+ 32
and
- 5
will do that job for you.
Add
5
5
to both sides of the equation.
√
2
x
+
13
=
x
+
5
2
x
+
13
=
x
+
5
To remove the radical on the left side of the equation, square both sides of the equation.
(
√
2
x
+
13
)
2
=
(
x
+
5
)
2
(
2
x
+
13
)
2
=
(
x
+
5
)
2
Simplify each side of the equation.
2
x
+
13
=
x
2
+
10
x
+
25
2
x
+
13
=
x
2
+
10
x
+
25
Solve for
x
x
.
x
=
−
2
,
−
6
x
=
-
2
,
-
6
Exclude the solutions that do not make
√
2
x
+
13
−
5
=
x
2
x
+
13
-
5
=
x
true.
x
=
−
2
M=c/at
Divide both sides by a and t to isolate m. Then the solution is just m=c/at
So we gots apolynomial equation that is 3rd degree and crosses x axis at x=-1, x=0 and x=2
the factors of a poly equation that passes through r1,r2,r3 is
(x-r1)(x-r2)(x-r3)
so
r1=-1
r2=0
r3=2
f(x)=(x-(-1))(x-0)(x-2)
f(x)=(x+1)(x)(x-2)
f(x)=x³-x²-2x
leading coefient is posiitve because 3rd degree equations that are postive go bottom left to top right
yah
actually that looks like the exact graph
both
f(x)=(x+1)(x)(x-2)
and
f(x)=x³-x²-2x
are correct
Answer:
c
Step-by-step explanation:
math